Morphological characteristics and permeability evolution of deep mine gas drainage boreholes - Liu, Xiao; Jing, Tianxiang; Lin, Haixiao; Xuan, Dequan; Li, Yong; Xu, Sen (Frontiers in Earth Science, 2022)
The structural coal has low permeability and high gas content, and it is expanding with the mining depth, which seriously restricts the safe mining of deep mine. Hydraulic punching is the main technical way to control structural coal gas. The shape of hydraulic flushing hole is an important basis to determine the pumping radius, which is equivalent to a cylinder. However, due to the difference of stress level, efflux and external moisture, the pore morphology and permeability evolution need to be further studied. At present, the hole shape of hydraulic punching is equivalent to a cylinder in drilling design and evaluation, which is one of the important basis for determining the effective extraction radius. However, the hole shape is affected by many factors, so the scientificity of equivalent to a cylinder remains to be discussed. The BR-PKN equation describing the hole shape is established by introducing and combining Bergmark Roos equation and PKN model, and the hole shape is reproduced by MATLAB; In order to verify its accuracy, YZD18.5 is used on site logging tool for data acquisition and analysis, and the hole section is drawn. The BR-PKN equation and permeability evolution model were simulated by COMSOL Multiphysics, and the permeability evolution law of conventional cylinder with hydraulic flushing was compared and analyzed The results show that :(1) the shape of hydraulic punch hole is ellipsoid with three different axes, and its horizontal section is approximately ellipse. (2) In the influence range of quasi-ellipsoid holes, the permeability changes in the long and short axis of quasi-ellipsoid holes are similar. The permeability evolution curve of coal increases first, then decreases, and finally flattens with the increase of distance from borehole. With the extension of extraction time, the permeability of coal body increases. (3) The permeability of the equivalent ellipsoid pore decreases with the increase of coal water content. The effective radius in the long and short axes of the minimum cross-section of the quasi-ellipsoid hole is 0.89 and 0.95 times of the effective extraction radius of the equivalent cylinder， which provides a basis for drilling layout.